1999
DOI: 10.1002/(sici)1520-6327(1999)41:4<214::aid-arch5>3.3.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Food intake in Blattella germanica (L.) nymphs affects hydrocarbon synthesis and its allocation in adults between epicuticle and reproduction

Abstract: The causal relationship between food intake and hydrocarbon synthesis was examined in vivo and in vitro. Fed Blattella germanica (L.) nymphs synthesized hydrocarbons in a stage-specific manner, with high rates occurring in the first 6 days of a 13-day last stadium, in relation to feeding. A similar pattern was exhibited in vitro by sternites and tergites from fed nymphs. In contrast, starved nymphs synthesized hydrocarbons at normal rates for the first 2 days, but then synthesis declined and ceased by day 6. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…Direct evidence for an allocation trade‐off between CHCs and fecundity in D. serrata has not been addressed but does exists in D. melanogaster . Gene‐knockout studies have shown a shared genetic basis for CHCs and egg production (Wicker and Jallon 1995) that likely arises because the cuticle and ovaries appear to compete for a common pool of internal hydrocarbons in insects (Schal et al 1994; Young et al 1999), possibly because oenocytes (specialized cells responsible for CHC expression; Billeter et al 2009) are also involved in lipid storage and metabolism (Gutierrez et al 2007). Adaptation to severe desiccation stress in D. melanogaster has also been shown to cause significant changes in CHCs in females, along with a corresponding decrease in fecundity (Kwan et al 2008; Kwan and Rundle 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Direct evidence for an allocation trade‐off between CHCs and fecundity in D. serrata has not been addressed but does exists in D. melanogaster . Gene‐knockout studies have shown a shared genetic basis for CHCs and egg production (Wicker and Jallon 1995) that likely arises because the cuticle and ovaries appear to compete for a common pool of internal hydrocarbons in insects (Schal et al 1994; Young et al 1999), possibly because oenocytes (specialized cells responsible for CHC expression; Billeter et al 2009) are also involved in lipid storage and metabolism (Gutierrez et al 2007). Adaptation to severe desiccation stress in D. melanogaster has also been shown to cause significant changes in CHCs in females, along with a corresponding decrease in fecundity (Kwan et al 2008; Kwan and Rundle 2009).…”
Section: Resultsmentioning
confidence: 99%
“…; Wicker and Jallon ; Young et al. ; Blows ; Holman ). If CHCs trade‐off with fecundity in T. oceanicus , and genetic variance in allocation between CHCs and fecundity exists, we would expect this to manifest in negative genetic correlations (Roff ).…”
Section: Methodsmentioning
confidence: 99%
“…The amount of food provided represents a restricted diet, being 56% of the average consumption. Although we were primarily interested in whether genetic correlations exist between fecundity and CHCs, female ornaments are predicted to trade-off with fecundity (Fitzpatrick et al 1995;LeBas 2006), and previous studies have provided evidence for a trade-off between CHCs and egg production in insects (Schal et al 1994;Wicker and Jallon 1995;Young et al 1999;Blows 2002;Holman 2012). If CHCs trade-off with fecundity in T. oceanicus, and genetic variance in allocation between CHCs and fecundity exists, we would expect this to manifest in negative genetic correlations (Roff 2002).…”
Section: Breeding Designmentioning
confidence: 99%
“…Maternal hydrocarbons would thus offset such deficiencies and serve to protect young nymphs from excessive water loss. Moreover, only a fraction of each intermolt period is dedicated to hydrocarbon synthesis (Fig.·2B) (Cripps et al, 1988;Young and Schal, 1997) and this process is significantly constrained by both availability of food (Young et al, 1999) and cyclic cellular competency of the oenocytes to produce hydrocarbons . Interestingly, the first instar of the German cockroach is the only mobile stage that can proceed to the next molt largely independent of food intake (Kopanic et al, 2001).…”
Section: Discussionmentioning
confidence: 93%
“…Of the remaining maternal hydrocarbons (34.3% of the total 14 C-hydrocarbons), 9.9% was then found on the cuticular surface of the second-instar nymph (equivalent to only 28.9±0.9% of radiolabeled hydrocarbons of the nymph) whereas 24.4% of the total maternal hydrocarbons (71.1±0.9% of radiolabeled nymphal hydrocarbons) were allocated to the internal hydrocarbon pool (Fig.·3A). Because internal -including maternal -hydrocarbons continue to be shunted to the cuticular surface throughout each intermolt period (Young et al, 1999), it is not surprising that ~16.6% of maternal hydrocarbons are lost after the second molt, and this loss is expected to continue in successive molts of well-fed insects. Nevertheless, the steady-state hydrocarbon composition of early nymphs suggests a 'last in/first out' hypothesis, whereby maternal hydrocarbons (first in) tend to be more retained internally than are newly biosynthesized nymphal hydrocarbons, which are more rapidly externalized.…”
Section: Fate Of Maternally Provisioned Hydrocarbonsmentioning
confidence: 97%